Направленное формирование свойств изделий машиностроения - Васильев А. С. Александр Сергеевич; Дальский А. М. Антон Михайлович; Золотаревский Ю. М. Юрий Михайлович; Кондаков А. И. Александр Иванович; Кондаков А. И. (Москва, Машиностроение, 2005)
175 -летию МГТУ им. Н. Э. Баумана посвящается.